2010
DOI: 10.3727/096368909x480927
|View full text |Cite
|
Sign up to set email alerts
|

Continuous and High-Level in Vivo Delivery of Endostatin from Recombinant Cells Encapsulated in TheraCyte® Immunoisolation Devices

Abstract: Endostatin (ES) is a potent inhibitor of angiogenesis and tumor growth. Continuous ES delivery of ES improves the efficacy and potency of the antitumoral therapy. The TheraCyte system is a polytetrafluoroethylene (PTFE) semipermeable membrane macroencapsulation system for implantation of genetically engineered cells specially designed for the in vivo delivery of therapeutic proteins, such as ES, which circumvents the problem of limited half-life and variation in circulating levels. In order to enable neovascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…As one trial to tackle the absorption, it is necessary to optimize the materials for the pouched-device in terms of low absorption property and high biocompatibility [33] , [34] , [35] . It is reported that the pouched-devices have a property to induce vascularization in the transplantation site [35] , [36] , [37] . Base on them, the PTFE membrane was used in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…As one trial to tackle the absorption, it is necessary to optimize the materials for the pouched-device in terms of low absorption property and high biocompatibility [33] , [34] , [35] . It is reported that the pouched-devices have a property to induce vascularization in the transplantation site [35] , [36] , [37] . Base on them, the PTFE membrane was used in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Throughout the two-month study, constant and high endostatin levels of up to 3.7 μg/ml were detected in the plasma of the mice implanted with the devices [15]. The use of CHO engineered cells, which apparently are more resistant than LM to the hypoxic microenvironment of the immunoisolation devices is other alternative to keep endostatin serum levels.…”
Section: Discussionmentioning
confidence: 99%
“…A commonly used commercial macrocapsule is the TheraCyte device, which is made of bilayered polytetrafluoroethylene (PTFE) membranes (Sörenby et al, 2008;Malavasi et al, 2010;Kirk et al, 2014). The outer membrane of the TheraCyte device is designed for strength and to facilitate neovascularization, and the inner membrane provides immune protection.…”
Section: Current Approachesmentioning
confidence: 99%